Do sibling correlations in skills, schooling, and earnings vary by socioeconomic background? Insights from Sweden - Erika Forsberg; Akib Khan; Olof Rosenqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
Family background shapes individual outcomes throughout life. While the existing literature documents how the importance of family background, typically measured by the degree of sibling correlation in socioeconomic outcomes, varies across countries, less is known about heterogeneities across social groups within a country. Using Swedish register data, we compare sibling correlations in skills, schooling, and earnings across fine-grained groups defined by parental socioeconomic status (SES). We find that sibling correlations generally decline in parental SES. This pattern holds for skills, schooling, and earnings, and is robust to alternative definitions of parental SES. These results align with theories suggesting that parental investments reinforce disparities, although other mechanisms such as complementarities between parental investments and child ability could also be at play. While the exact mechanisms behind the observed socioeconomic gradient in sibling similarity are hard to identify, the results suggest that life is more formed by individual endowments and considerations for children from high SES backgrounds as compared to their low SES counterparts.
Keywords: I24; J24; J62; 330; sibling correlations; education; earnings; skills; parental socioeconomic status